Demonstration of a Periodic Passband Filter Based on Coupled Microfiber Knots - Nodehi, S.; Mohammed, W.S.; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In this letter, a periodical passband filter based microfiber structure is proposed. The structure is made of successive microfiber knot resonators. The periodical spectral filtering is a result of superposition of the uncoupled modes that belong to the individual microfiber knots and coupling induced resonant wavelength shift. This letter demonstrates the experimental investigation of the thermal effect on the spectral modulation of the structure. The proposed resonator consists of two knots with radii 460.01 and 230 μm, which are knitted successively, in a column. This results in a periodic spectrum with 720-pm passband, 425-pm stopband, and a suppression ratio of 5.2 dB. Increasing the optical path, using a hot metal bar with a temperature of 30° close to the big knot, the periodic passband filter switches to all pass filter with a free spectral range of 1150 pm and quality factor 6000. This letter as well demonstrates experimentally how to enhance passband and stopband widths through decreasing the knot's radii as well as increasing the number of knots. Compatibility of this structure with single-mode fiber systems makes it easy to be used as noise filtering in telecommunication and fiber lasers.